Relationship between Body Composition and Bone Mineral Density in Healthy Postmenopausal Chinese Wowen in Malaysia - , Winnie Chee Siew Swee; Tein, Geik Poh; Tan, Soon Yean; Chan, Siew Peng; Zaitun Yassin,; Suriah Abdul Rahman, (penerbit ukm, 2007)
Bone loss is known to be accelerated during menopause. The postmenopausal period with advancing age has also been associated with a decrease in learn body mass, an increase in body fat mass and increase in body weight. This study investigated the relative contribution of lean body mass and body fat mass to bone mineral density (BMD) in 139 healthy postmenopausal Chinese women in Kuala Lumpur. Total body, lumbar spine (L2-L4), femoral neck and total hip BMD were measured using dual-energy X-ray absorptiometry (DXA). Findings revealed that 80% of the Chinese postmenopausal women had low bone mass (osteopenia) and 8% were osteoporotic at the lumbar spine and/or femoral neck. Overall, body fat mass showed a positive correlation with BMD at all sites (total body, r = 0.265, p<0.001; total hip r =0.332, p<0.001). Similarly, lean body mass was positively correlated with BMD at most sites (Total body r = 0.239, p < 0.001; femoral neck r = 0.365, p<0.001; total hip r = 0.352, p<0.001) except the lumbar spine. In a multiple stepwise regression analysis body fat mass was a significant predictor for BMD for total body (p<0.0001) and lumbar spine (p<0.005) BMD, while lean body mass was the major determinant of BMD at the femoral neck and total hip (p<0.0001). These data suggested that both fat and lean mass were significant determinants of BMD, the former playing a greater role than lean mass in postmenopausal women. Therefore, postmenopausal women need to avoid being too underweight (and thus having too low body fat) and to maintain lean body mass to protect against osteoporosis